2022
DOI: 10.1177/24705470221083866
|View full text |Cite
|
Sign up to set email alerts
|

The Swedish HealthPhys Study: Study Description and Prevalence of Clinical Burnout and Major Depression among Physicians

Abstract: Objectives The study purpose was to describe the Swedish HealthPhys cohort. Using data from the HealthPhys study, we aimed to describe the prevalence of clinical burnout and major depression in a representative sample of Swedish physicians across gender, age, worksite, hierarchical position, and speciality in spring of 2021, during the third wave of the Covid-19 pandemic. Method The HealthPhys questionnaire was sent to a representative sample of practising physicians (n = 6699) in Sweden in February to May of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Other Swedish studies have found comparable burnout levels (both total burnout score and the four sub‐dimensions) among Swedish midwives in a national cohort with data collection in April 2020, just before the full effect of the pandemic hit Sweden 30 . Similar proportions scoring above critical clinical burnout levels were found in a representative sample of Swedish physicians during the third wave of the pandemic 31 . Similar effects have also been found among MNHCWs in other countries during the pandemic, 4–7,9,32 although direct comparisons were impossible because of major methodologic differences.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Other Swedish studies have found comparable burnout levels (both total burnout score and the four sub‐dimensions) among Swedish midwives in a national cohort with data collection in April 2020, just before the full effect of the pandemic hit Sweden 30 . Similar proportions scoring above critical clinical burnout levels were found in a representative sample of Swedish physicians during the third wave of the pandemic 31 . Similar effects have also been found among MNHCWs in other countries during the pandemic, 4–7,9,32 although direct comparisons were impossible because of major methodologic differences.…”
Section: Discussionsupporting
confidence: 60%
“…30 Similar proportions scoring above critical clinical burnout levels were found in a representative sample of Swedish physicians during the third wave of the pandemic. 31 Similar effects have also been found among MNHCWs in other countries during the pandemic, [4][5][6][7]9,32 although direct comparisons were impossible because of major methodologic differences.…”
Section: Discussionmentioning
confidence: 58%
“…A recent Swedish study shows that Swedish physicians experienced extremely high levels of exhaustion during the peak of the second wave of the COVID-19 pandemic (Hagqvist et al, 2022). Studies from other countries confirm these figures (De Sio et al, 2020;Leo et al, 2021;Restauri and Sheridan, 2020) and link them to the many unprecedented working demands during the pandemic (Billings et al, 2021;de Wit et al, 2020).…”
Section: Introductionmentioning
confidence: 93%
“…A recent Swedish study shows that Swedish physicians experienced extremely high levels of exhaustion during the peak of the second wave of the COVID-19 pandemic (Hagqvist et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The LOHHCS cohort included a sample of practicing physicians, registered nurses, and assistant nurses in Sweden. For more information, see Hagqvist et al (35).…”
Section: Study Design Study Participation and Data Collectionmentioning
confidence: 99%